Generalized Analysis of English Language Importance in Linguistics Languages History - G.M.C.M.Dayananda (International Journal of Intelligent Systems and Applications in Engineering, 2024)
During the British Empire's continental expansion, English became established in nations in Africa, Asia, and the Americas. The groundwork for English's function as a bridge language in many former colonies was established by this historical effect. In a worldwide environment, English language instruction naturally undergoes modifications. A significant number of students have begun studying English as a foreign and second language as a result of globalization. Gaining proficiency in English increases international cooperation, understanding, and development by providing people and nations with access to global opportunities. This research paper looks at the historical evolution of the English language and its importance in the study of linguistics. English is now the most widely spoken language in the world and is essential to sociolinguistic studies, linguistic theory, and language research. English provides important insights into linguistic diversity, contact phenomena, and evolution from its beginnings as a Germanic language to its current position as the world's common tongue. An overview of the significance of English in linguistic studies, historical evolution, linguistic variety, and the digital age is given in this study. The writers have conducted linguistic studies of the English language and offer insightful analyses of a number of basic linguistic concepts, including phonetics, syntax, semantics, morphology, and sociolinguistics. Additionally, this essay emphasizes the significance of the sometimes-overlooked distinction between general linguistics—the study of human language—and particular linguistics—the study of individual languages. The detail analysis and importance of the English language is consolidated in this paper that referred to various fields such as; applied linguistic, historical linguistic, sociolinguistic and computational linguistic. However,